The result of an evaluation for traffic flow characteristics considering the movement of personal mobility equipment by modeling a road traffic section - A. A. Jung; A. G. Shevtsova (Вестник СибАДИ, 2022)
Introduction. Today there is an acute problem of increasing the number of accidents involving personal mobility devices (PMD). A sharp increase in these vehicles on public roads poses a threat to both vehicle drivers and pedestrians.Materials and methods. In this article, the results of the evaluation of the traffic flow characteristics of individual mobility devices under different conditions with the help of road section modelling are presented. The aim of the study is to obtain real values of traffic flow characteristics for further analysis and comparison, which in the future will reduce the accident rate with the participation of personal mobility devices. It is suggested a modelling method to be used to analyse the characteristics of traffic flow changing with the introduction of these devices. The objectives of the study are to analyse the number and types of accidents involving personal mobility devices, to identify conflict zones in the interaction of personal mobility devices with other road users, and to select the road environment to be modelled. Both positive and negative aspects of the introduction of PMD in everyday life are presented, and the main types and characteristics of personal mobility devices are briefly considered. Aimsun simulation software was used to create models of a road network section with the introduction of mobility devices in various traffic situations to evaluate their impact on traffic flow.Results. A road section model has been created to automate information processing and to consider different situations of PMD movement in an urban environment, which will allow further comparative analysis to select the safest conditions for the movement of these vehicles.Discussion and conclusions. The use of this modelling method will increase the speed of the study and help to determine most clearly how traffic flow characteristics change in the situations presented.